Economic Viability of the Production of Peruvian Grunt (Anisotremus scapularis) in RAS on the Peruvian–Chilean Desert Coast - Pablo Presa; Yolanda Leonor Perca Cruz; Jordan I. Huanacuni; Renzo Pepe-Victoriano; Luis A. Espinoza-Ramos (Animals)
The Peruvian grunt Anisotremus scapularis is one of the most appreciated fish in Peruvian national markets. However, its reduced and irregular fishery is a paradigm of illegal, unreported, and unregulated fishing (IUU) in the Peruvian–Chilean coastal region. An important technological advancement has been achieved in the last decade in capture, management, nutrition, and broodstock maintenance to boost pilot experiences on the aquaculture of this species. Therefore, it is pertinent to evaluate the economic viability of this candidate species to identify cultivation bottlenecks, optimize the process, and assess the transfer feasibility of the technical know-how to interest groups. In this study, we performed a sensitivity analysis to assess how market price and production size should make its commercialization profitable. We show that the use of photovoltaic solar panels and a raw production cycle of 15 months enables profitability at a ~400 k unit farm size at a commercial market price of 6.67 USD/kg, i.e., B/C = USD 1.14. Both, time to market and market price exerted the highest influence on the value of grunt farms; whereas, a reduction of the production cycle to 12 months by seed selection, optimized rearing conditions, and nutritional diets also provides a profitable investment, i.e., NPV = USD 287,054 with an IRR = 23.71% at a discount rate of 10% and B/C = USD 1.15. These scenarios pave the way for the transfer of technological know-how to entrepreneurial initiatives in the economically depressed coastal region of the Atacama Desert.